Microbial contamination of cosmetics and the pharmaceutical products, and their preservation strategies: A comprehensive review - Souvik Roy; Saheli Majumder; Aniket Deb; Lopamudra Choudhury (Novel Research in Microbiology Journal, 2023)
A brief discussion of the numerous types of microbial contamination of the pharmaceutical and cosmetic items and their corresponding effects is attempted in this study. The pharmaceutical and cosmetic products are particularly vulnerable to microbial contamination, because they contain chemical compounds that encourage the microbial development. Contamination can potentially happen during production; storage, and/ or usage. These contaminants can cause a variety of unfavorable effects, including alteration of the consistency and appearance; phase separation, alteration or loss of activity, and even the emergence of toxicity in the contaminated items. Organizations such as the United States Food and Drug Administration (FDA) actively regulate the consumer safety by frequently recalling the potentially dangerous or contaminated products from the market. Therefore, to prevent microbial contamination and increase the shelf life of a product, a variety of preservatives are added to the final formulation. However, some of these preservatives may be toxic to the consumer as well. In this context, we have also reviewed the mechanisms of action of some of the most commonly used antimicrobial preservatives, including the organic acids; parabens, phenol, organomercurials, ethanol, chlorobutanol, benzalkonium chloride, chlorocresol, sodium benzoate, isothiazolinones, sodium sulfite, and sodium metabisulfite, in addition to the potential toxicity caused by them to the consumers.